ANALISIS KEJENUHAN BELAJAR SISWA KELAS V DAN VI PADA SEKOLAH DASAR SD NEGERI 43 JAMBI - Helisa, Helisa Nia Anjani; Sri Mulyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this writing is to determine the effect of boredom on students' concentration abilities and how to overcome boredom in student learning. This study uses a qualitative method. This research uses library research which uses documents to combine information and data such as books, news and magazines. This research also uses non-examination methods by interviewing students and their teachers. The results of this research show that students' boredom in concentrating on learning is influenced by environmental factors that are less supportive, and the use of methods used by teachers in implementing learning that are ineffective, diversity and lack of student motivation to learn. The conclusion of this research is that students' boredom while studying has a significant influence on their ability to concentrate while studying. Apart from how to overcome boredom in student learning well and maximally, to reduce boredom in learning which has a big impact on students, there are many things that can be overcome by teachers themselves and students.